Gap symmetry and charge density excitations in high-Tc superconductors with extended saddle points in electron spectrum - Pashitskii, E.A.; Pentegov, V.I.; Semenov, A.V. (Condensed Matter Physics, 1999)
It is shown that the strong anisotropy of the one-particle electron spectrum, due to the presence of extended saddle-point features (ESPF) close to the Fermi level in the hole-type cuprates YBCO and BSCCO, leads to the occurrence of a low-frequency peak in the spectral function of the charge density ﬂuctuations due to the presence of acoustic plasmon branch in the collective electron spectrum. The retarded anisotropic electron-plasmon interaction leads to the suppression of the static screened Coulomb repulsion for small transferred momenta and, consequently, to the effective attraction between electrons in the dx²-y²-wave channel of the Cooper pairing of current carriers. Breaking of C₄v symmetry in YBCO crystals leads to a possibility of a change of dx²-y²-wave symmetry of the gap to a mixed s − d gap symmetry for singlet Cooper pairs or to a p-wave gap symmetry for triplet pairs.